1993
DOI: 10.1172/jci116235
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of phosphotyrosine-containing proteins, platelet-derived growth factor-B, and fibroblast growth factor-1 in situ in synovial tissues of patients with rheumatoid arthritis and Lewis rats with adjuvant or streptococcal cell wall arthritis.

Abstract: Fibroblast growth factor (FGF)-l and PDGF-B-like factors have been implicated in the pathobiology of RA and animal models of this disease. Since the receptors for FGF-1 and PDGF are tyrosine kinases, we examined the expression of tyrosine phosphorylated proteins (phosphotyrosine, P-Tyr) in synovial tissues from patients with RA and osteoarthritis (OA), and rats with streptococcal cell wall (SCW) and adjuvant arthritis (AA). Synovia from patients with RA and LEW/ N rats with SCW and AA arthritis, in contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…PDGF-C and PDGF-D were detected in the synovial lining layer, diffuse infiltrates, and stroma of the SM, according to the expression previously reported for PDGF-A and PDGF-B (13,15); this leads to the assumption that cells of these compartments are able to express all isoforms of PDGF. Double-labeling experiments with specific markers showed expression of both PDGF-C and PDGF-D by synovial fibroblasts and macrophages, which is consistent with recent findings of PDGF-C in dermal and lung fibroblasts (25) and in infiltrating inflammatory CD11bϩ cells in coxsackievirus B3-induced chronic myocarditis (26).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…PDGF-C and PDGF-D were detected in the synovial lining layer, diffuse infiltrates, and stroma of the SM, according to the expression previously reported for PDGF-A and PDGF-B (13,15); this leads to the assumption that cells of these compartments are able to express all isoforms of PDGF. Double-labeling experiments with specific markers showed expression of both PDGF-C and PDGF-D by synovial fibroblasts and macrophages, which is consistent with recent findings of PDGF-C in dermal and lung fibroblasts (25) and in infiltrating inflammatory CD11bϩ cells in coxsackievirus B3-induced chronic myocarditis (26).…”
Section: Discussionsupporting
confidence: 59%
“…Synovial cells located in pannus show an invasive behavior, are of variable cell size (11), and express high levels of protooncogenes (12) and tyrosine phosphorylated proteins (13). PDGF receptor (PDGFR) ␣ and ␤ chains are detected in fibroblast-like cells in the inflamed synovial membrane (SM) (14).…”
mentioning
confidence: 99%
“…Positive staining was indicated by brownish deposits. Double antibody staining with anti-S1P 1 antibody and anti-COX-2 antibody was performed as previously described (32). For S1P 1 staining, the color was developed with a DAB solution including 0.04% (w/v) nickel chloride.…”
Section: Methodsmentioning
confidence: 99%
“…For each tissue specimen from the RA and OA patients, the extent and intensity of anti-SP-1P 1 staining in synovial lining cells, inflammatory mononuclear cells, and vascular endothelial cells was graded on a scale of 0-4ϩ by 2 blinded observers on 2 separate occasions, using coded slides as previously described (21,(30)(31)(32). The observer assigned the scores after assessment of the entire tissue section, such that a grade of 4ϩ indicated that staining was maximally intense throughout the specimen, while a grade of 0 indicated that staining was absent throughout the specimen.…”
Section: Methodsmentioning
confidence: 99%
“…The synovial hyperplasia is probably due to stimulation by various growth factors, such as IL-1, fibroblast growth factor (FGF) and platelet-derived growth factor (PDGF) [4][5][6][7]. PDGF-BB is locally produced in the RA synovium and may play an important role in the pathogenesis of RA [7,8]. In the present study we examined the PDGF-mediated intracellular signal transduction in synovial cell growth.…”
Section: Introductionmentioning
confidence: 99%